Healing stress in military families : eight steps to wellness - DeCarvalho, Lorie T.; Whealin, Julia M. (Hoboken, N.J. : John Wiley & Sons, 2012)
'There are 1.7 million American children who have at least one parent serving in the military. Family members are left to cope with everyday life while worrying about the health and well-being of someone thousands of miles away in a war zone. Based on the latest scientific research and best practice guidelines, this timely book offers pertinent, practical help for military families. Integrating more than thirty-five years of clinical experience in treating veterans and their families, this is a useful guide for clinicians, active duty service members, veterans, and family members'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Family psychotherapy -- United States; Stress (Psychology) -- United States; Military psychiatry -- United States